Sex Differences in Rotenone Sensitivity Reflect the Male-to-Female Ratio in Human Parkinson's Disease Incidence. (25th March 2019) - De Miranda, Briana R; Fazzari, Marco; Rocha, Emily M; Castro, Sandra; Greenamyre, J Timothy
Abstract: There is a critical need to include female subjects in disease research; however, in Parkinson's disease, where the male-to-female incidence is about 1.5-to-1, the majority of preclinical research is conducted in male animals. The mitochondrial complex I inhibitor, rotenone, is selectively toxic to dopaminergic neurons, and reproduces several neuropathological features of Parkinson's disease, including α-synuclein pathology. Rotenone has been primarily utilized in male Lewis rats; however, pilot studies in age-matched female Lewis rats revealed that our usual dose (2.8 mg/kg/day intraperitoneal [ i.p. ]) did not cause dopaminergic neurodegeneration. Therefore, we compared rotenone-treated males (2.8 mg/kg/day, i.p. ) to females at increasing doses (2.8 mg/kg/day, 3.2 mg/kg/day, 3.6 mg/kg/day, and 1.6 mg/kg bis in die, i.p. ). Female rats receiving 3.2 mg/kg, and 3.6 mg/kg rotenone displayed significant loss of dopaminergic neurons in the substantia nigra as assessed by stereology, which was accompanied by a loss of striatal dopaminergic terminals. Even at these higher doses, however, females showed less inflammation, and less accumulation of α-synuclein and transferrin, possibly as a result of preserved autophagy. Thus, the bias toward increased male incidence of human Parkinson's disease is reflected in the rotenone model. Whether such sex differences will translate into differences in responses to mechanism-driven therapeutic interventions remains to be determined.